Comparison of Nutritional Content of Mangifera indica L. var. Wirasangka with Three Other Varieties in Tegal Regency - Rahayu, Enni Suwarsi; Retnoningsih, Amin; Abdullah, Muhammad; Susanti, Priyanti (Biosaintifika: Journal of Biology & Biology Education, 2020)
Mangifera indica L. var. wirasangka or wirasangka mango, a local plant in Tegal Regency, has a low population because it is rarely planted by people as its unknown nutritional content. To increase people's interest in planting, it is necessary to know the nutritional content of wirasangka mango. The aim of the study was to compare the nutritional content of wirasangka mango with three other varieties in Tegal Regency. This study used a one-factor completely randomized design. The factor was the mango variety which included six varieties, namely the varieties of wirasangka from three areas, okyong, tengkoeh, and golek. The variables observed were content of water, fiber, fructose, Î²-carotene, potassium and iron, as well as vitamin C and antioxidant activity. Normally distributed data were analyzed using One-Way Analysis of Variance and Least Significant Difference (LSD) test. Besides, the non-normally distribution data were analyzed using Kruskal Walis and continued with post-hoc test, i.e. Mann-Whitney. The results showed that the levels of water, dietary fiber, fructose, Î²-carotene, and iron were significantly different at the significance level of 0.1. Wirasangka mango has a higher fiber, and fructose content, but lower of Î²-carotene and iron content compared to okyong, tengkoeh and golek mangoes. The levels of vitamin C, potassium, and antioxidant activity of wirasangka mango were equivalent to the three other varieties studied. Thus the wirasangka mango has advantages which are expected to increase the interest of people in Tegal Regency to plant this variety. As a result, its population in the future will also increase.